Enhancing widening participation evaluation through the development of a selfassessment tool for practitioners: learning from the OfS project Standards of Evaluation Practice (Phase 2) 2017–2019. (1st July 2020) - Mountford-Zimdars, Anna; Moore, Joanne; Shiner, Richard
The ultimate goal of widening participation work, which unites policymakers, practitioners and academics, is to enhance the experience of disadvantaged students relating to HE access, success and outcomes. This article presents the Office for Students' (OfS) commissioned project Standards of Evaluation Practice (Phase 2). This project sought to create a step-change in robustness of evidence used and evaluation practices. Our 2017 – 19 project explored evaluation practices among nine partner organisations drawn from higher education providers (HEPs) and third-sector partners. The initial aim was to pilot test the Standards of Evidence of Evaluation developed during Phase 1 research; share practices that work and highlight examples of best practice. As the project developed, a further outcome was envisaged through ongoing discussions between the OfS, academics, HEPs and third-sector parties: a self-assessment tool for evaluation practitioners. This tool provides a framework and guidance which allow practitioners to map their own evaluation approaches. Through using prompts, the five dimensions of the tool highlight strengths and weaknesses of evaluation within five domains (strategic context, programme design, evaluation design, evaluation implementation and learning). This new tool is, in effect, a five-point framework setting guidance about good evaluation practice. It was rolled out to all HEPs in spring 2019, when providers were invited to return the completed tool and their reflection as part of their access and participation planning.